Multiple sclerosis in the north Cambridgeshire districts of East Anglia. Issue 1 (July 1995) - Robertson, N; Deans, J; Fraser, M; Compston, D A
Abstract : The Cambridgeshire multiple sclerosis register was established in 1989 and initially reported a prevalence of 130/10(5) population for south and east Cambridgeshire (south Cambs). This survey has now been extended to the northern county districts where there were 449 patients with multiple sclerosis in population of 378, 959 on 1 July 1993 (118/10(5); 95% confidence interval (95% CI) 108-130). Four hundred and four had either definite or probable disease (107/10(5); 95% CI: 98-118). This matches the highest figures in the series of seven epidemiological surveys carried out in southern England over the past decade. Comparison with these and other studies indicates that no latitudinal gradient of disease is found in southern England despite spanning four degrees of latitude.